Behavioristic Group Counseling Contingency Contracting Techniques In Reducing Teenage Bullying In Islamic Boarding Schools - Almizri, Wahyu; Firman, Firman (Journal of Educational Science and Technology (EST), 2024)
The aim of this research is to test the effectiveness of behavioristic group counseling using contingency contracting techniques in reducing bullying among Islamic boarding school teenagers. This research uses a single case experimental design experimental method with an AB design. The subjects in this research were ten students from class VIII . Data collection techniques used Islamic boarding school youth instruments. Data analysis using Wilcoxon Signed Ranks t Test . The results of statistical analysis using the Wilcoxon Signed Ranks t test showed differences in the intervention conditions compared to the baseline phase . Of the 10 experimental group respondents who were involved in the calculations, 10 people in line experienced a decrease from pretest to posttest. This is evidenced by subjects trying to reduce the frequency of carrying out bullying behavior . So it can be concluded that behavioristic group counseling using contingency contracting techniques is effective for reducing bullying among Islamic boarding school teenagers.